Early Loss of the Glucagon Response to Hypoglycemia in Adolescents with Type 1 Diabetes - Siafarikas, A.; Johnston, R.; Bulsara, M.; O'Leary, Peter; Jones, T.; Davis, E. (American Diabetes Association, 2012)
Objective: To assess the glucagon response to hypoglycemia and identify influencing factors in patients with type 1 diabetes compared with nondiabetic control subjects.Research design and methods - Hyperinsulinemic hypoglycemic clamp studies were performed in all participants. The glucagon response to both hypoglycemia and arginine was measured, as well as epinephrine, cortisol, and growth hormone responses to hypoglycemia. Residual ß-cell function was assessed using fasting and stimulated C-peptide.Conclusions - The glucagon response to hypoglycemia in adolescents with type 1 diabetes is influenced by the duration of diabetes and can be lost early in the course of the disesase.